ONLINE WORD OF MOUTH ON INDONESIAN BEHAVIOUR IN MALAYSIAN HEALTHCARE SERVICES - Khair, Hazmanan; Erlinda, Erlinda; Ladewi, Yuhanis (Accounting and Business Journal, 2020)
Purpose –The purpose of this study was to examine the effect of online word of mouth on the medical treatment of Indonesians in Malaysian hospitals. Design/methodology/approach – The analysis of 401 patients from Indonesia who had undergone medical treatment in Malaysian hospitals was done using SPSS. A convenience sampling technique was used in this study. A total of 401 questionnaires were distributed. Findings - the intensity and content of online word of mouth related to purchase behaviour, while valence of online word of mouth not related to purchase behaviour (rejected). Research limitations/implications – This research examined the concept of word of mouth communication and online word of mouth communication.. However, this study did not explore offline word of mouth or traditional word of mouth communication. Practical implications –The results indicate that the source from experts was not as the main information source. Hospital managers should be using another method to share hospital information through social media (online) Originality/value – This study will enable hospital managers should use the information technology sophisticated to promote their services and then using the comment of medical expert as a stimulation media.